Impact of Timing following Acute Myocardial Infarction on Efficacy and Safety of Bone Marrow Stem Cells Therapy: A Network Meta-Analysis - Bei Liu; Chong-Yang Duan; Cheng-Feng Luo; Cai-Wen Ou; Zhi-Ye Wu; Jian-Wu Zhang; Xiao-Bin Ni; Ping-Yan Chen; Min-Sheng Chen (Stem Cells International)
Background. The optimal timing for Bone Marrow Stem Cells (BMCs) therapy following acute myocardial infarction (AMI) remains unclear. Aims. To synthesize the evidence from trials using a multiple-treatment comparison method, thereby permitting a broader comparison across multiple timing of BMCs therapy. Methods and Results. Randomized controlled trials in patients with AMI receiving BMCs therapy were identified from PubMed, Ovid LWW, BIOSIS Previews, and the Cochrane Library through January 2015. 2 035 patients of 31 studies included in our analysis were allocated to 5 groups’ treatments: 1~3 days, 4~7 days, 8~14 days, 15~30 days, or placebo/control group. The multiple-treatment meta-analysis showed that 4~7 days’ group could lead to significantly increased left ventricular ejection fraction (LVEF) as compared with control (mean of MDs and 95% CI: 6 months, 3.05 (0.92~5.25); 12 months, 4.18 (2.30~5.84)). Only 4~7 days led to significant reduction of MACEs compared with control (OR and 95% CI 0.34 (0.13~0.96)) for 12-months follow-up. In simulated comparisons, the 4~7 days’ group ranked better than other timing groups for improvement of LVEF or reduction of the incidence of major adverse cardiac events. Conclusions. 4~7 days after AMI might be the optimal timing for cell therapy in terms of efficacy or safety.